Forests Sourcebook : Practical Guidance for Sustaining Forests in Development Cooperation - World Bank (Washington, DC : World Bank, 2012)
The Forests Sourcebook is divided into two parts. The first contains an introduction to the book plus seven chapters covering topics associated with enhancing the contribution of forests to poverty reduction, engaging the private sector, meeting the growing demand for forest products, optimizing forest functions at the landscape level, improving forest governance, mainstreaming forest considerations into macro policy dialogue, and monitoring forest sector activities. Each chapter provides relevant background and context with a general overview of the fundamental issues, constraints, policies, and institutional requirements that need to be considered for specific topics. The second part provides guidance for implementing the World Bank's safeguard on forests. This section of the Forests Sourcebook has five chapters. Chapter eighth provides a brief introduction to the World Bank's Forests Policy (OP 4.36). Chapter ninth is on applying OP 4.36. This chapter includes a discussion of the main requirements of OP 4.36, guidelines for implementation (including preparation, appraisal, and supervision requirements), definitions, and guidance on identifying critical forests and critical natural habitats through environmental assessment, which includes a discussion on protecting forests through conservation offsets. Chapter tenth is on consultation and communication in forest projects. Chapters eleventh and twelfth discuss the Forest Certification Assessment Guide and the World Bank's Indigenous Peoples policy, respectively.